Evaluation of Native and Kadaknath chicken for production performance, egg quality traits and farmers acceptability in Western Himalayan region of Himachal Pradesh, India - DINESH, KRISHANENDER; SANKHYAN, V; THAKUR, D; KATOCH, S; KUMAR, S; BHARDWAJ, N (The Indian Journal of Animal Sciences, 2024)
The present study evaluated production performance and egg quality traits of native and Kadaknath chicken of Himachal Pradesh under sub-temperate western Himalayan region of India. External egg quality traits like egg weight, egg length, egg width, shell thickness and internal traits like length, height, width of albumen, yolk height, and yolk width were measured. Body weight of native and Kadaknath birds differed significantly at different age of measurements and body weight of native birds was significantly higher than Kadaknath. Age at sexual maturity was found less in native birds in comparison to Kadaknath. HHEP and HDEP was observed higher in native birds than Kadaknath. Mean value estimated for egg weight, egg length, egg width, shape index and shell thickness were 45.33 g, 54.99 mm, 41.27 mm, 75.02% and 0.36 mm, respectively in native eggs while corresponding values were 43.87 g, 53.61 mm, 40.80 mm, 76.20% and 0.34 mm, respectively in Kadaknath eggs. Albumen length, albumen width, yolk height and yolk index is observed significantly higher in native birds than Kadaknath. Appraisal of farm practices through field survey suggests that Kadaknath birds witnessed rising popularity in recent times. However, native birds of the region are better producers in comparison to Kadaknath. This suggests that native birds may be preferred over Kadaknath birds in similar regions where premium pricing of Kadaknath is unavailable. Occasionally peri-urban market offered opportunity of premium pricing based income through sale of Kadaknath birds. Thus, rearing of Kadaknath along with native birds is advised in such regions.